Correlation Analysis of Slaughter Weight and Body Dimensions on Bali Cattle Carcass Production Based on Sexes - Hafid, Harapin; Zelpina, Engki (JAS, 2025)
Carcass production in Bali cattle is an important indicator in the livestock industry, influenced by genetic and environmental factors, particularly live weight and body dimensions. However, studies comparing the contribution of slaughter weight and body dimensions to carcass production based on the sex of Bali cattle remain limited. This study aims to analyze the relationship between slaughter weight and body dimensions with carcass production in male and female Bali cattle in order to provide precise information for slaughter animal selection. The research was conducted using a survey method and direct measurements of slaughter weight, body dimensions (body length, withers height, and chest girth), and carcass production in 30 Bali cattle (15 males and 15 females) slaughtered at the Kendari City Slaughterhouse. Samples were randomly selected from the population of slaughter-ready cattle. The results showed that slaughter weight had a very strong correlation with carcass production in both male (r = 0.99) and female (r = 0.91) Bali cattle. Among all the measured body dimensions, chest girth showed the most significant influence on carcass production. In conclusion, slaughter weight is the main predictor of carcass production, and chest girth can be used as an additional indicator in selecting Bali cattle, regardless of sex. The contribution of this study is to provide deeper insight into the size-related factors affecting carcass productivity by sex, which can be utilized in breeding programs and livestock slaughter management.